Evaluation of Accounts Receivable Accounting and Its Relation to the Presentation of Financial Statements (Case Study at PDAM Tirta Silaupiasa, Asahan District) - Dini Azlina Pane; Rahmat Daim Harahap (Penerbit Jurnal Indonesia, 2022)
Credit sales are one of the ways companies do to expand and enlarge sales results. The company made credit sales which then resulted in receivables. The purpose of this research is to find out the sales process that occurs in the Regional Drinking Water Company (PDAM) Tirta Silaupiasa, Asahan Regency. Sales made by the Regional Drinking Water Company (PDAM) Tirta Silaupiasa, Asahan Regency, namely sales on credit, is a policy carried out by the Regional Drinking Water Company (PDAM) Tirta Silaupiasa, Asahan Regency to customers, with the aim of increasing sales volume. While the Regional Drinking Water Company (PDAM) Tirta Silaupiasa Asahan Regency itself uses the method of recording losses, namely by using the accrual basis method in accounting records in accordance with SAK-ETAP, this aims to minimize losses that usually occur. In addition, in the accrual basis method in accordance with SAK-ETAP, an estimate of the amount of losses on receivables that is charged to the customer in question is carried out at the end.